Emerging Concepts on the Gut Microbiome and Multiple Sclerosis - Glenn, Justin D. (J Interferon Cytokine Res, 2016)
Microbiota of the human body perform fundamental tasks that contribute to normal development, health, and homeostasis and are intimately associated with numerous organ systems, including the gut. Microbes begin gut inhabitance immediately following birth and promote proper gut epithelial construction and function, metabolism and nutrition, and immune system development. Inappropriate immune recognition of self-tissue can lead to autoimmune disease, including conditions such as multiple sclerosis (MS), in which the immune system recognizes and attacks central nervous system tissue. Preclinical studies have demonstrated a requirement of gut microbiota for neuroinflammatory autoimmune disease in animal models, and a growing number of clinical investigations are finding associations between MS status and the composition of the gut microbiota. In this review, we examine current undertakings into better understanding the role of gut bacteria and their phages in MS development, review associations of the gut microbiota makeup and MS, and discuss potential mechanisms by which the gut microbiota may be manipulated for therapeutic benefit.